Recurrent Amplification of the Heterochromatin Protein 1 (HP1) Gene Family across Diptera. (19th June 2018) - Helleu, Quentin; Levine, Mia T
Abstract: The heterochromatic genome compartment mediates strictly conserved cellular processes such as chromosome segregation, telomere integrity, and genome stability. Paradoxically, heterochromatic DNA sequence is wildly unconserved. Recent reports that many hybrid incompatibility genes encode heterochromatin proteins, together with the observation that interspecies hybrids suffer aberrant heterochromatin-dependent processes, suggest that heterochromatic DNA packaging requires species-specific innovations. Testing this model of coevolution between fast-evolving heterochromatic DNA and its packaging proteins begins with defining the latter. Here we describe many such candidates encoded by the Heterochromatin Protein 1 (HP1) gene family across Diptera, an insect Order that encompasses dramatic episodes of heterochromatic sequence turnover. Using BLAST, synteny analysis, and phylogenetic tree building across 64 Diptera genomes, we discovered a staggering 121 HP1 duplication events. In contrast, we observed virtually no gene duplication in gene families that share a common "chromodomain" with HP1s, including Polycomb and Su(var)3-9 . The remarkably high number of Dipteran HP1 paralogs arises from distant clades undergoing convergent HP1 family amplifications. These independently derived, young HP1s span diverse ages, domain structures, and rates of molecular evolution, including episodes of positive selection. Moreover, independently derived HP1s exhibit convergent expression evolution. While ancient HP1 parent genes are transcribed ubiquitously, young HP1 paralogs are transcribed primarily in male germline tissue, a pattern typical of young genes. Pervasive gene youth, rapid evolution, and germline specialization implicate heterochromatin-encoded selfish elements driving recurrent HP1 gene family expansions. The 121 young genes offer valuable experimental traction for elucidating the germline processes shaped by Diptera's many dramatic episodes of heterochromatin turnover.